Isolation, Molecular Detection and Phylogenetic analysis of Avipox Virus obtained from Pigeon - Rajasekaran, Ranjani; Kirubaharan, J. John; Shilpa, P.; Vidhya, M.; Rajalakshmi, S. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Dried scab material obtained from pigeon showing cutaneous form of avipox infection was inoculated in chorio-allantoic membrane (CAM) of 11-day old embryonated chicken egg. After an incubation of five days, CAM showed mild pock lesions. This CAM tissue was subjected to DNA isolation. Molecular confirmation of avipox virus was done by PCR amplification of P4b gene, which amplified at an expected product size of 578 bp. The amplified P4b gene was sequenced and phylogenetic analysis was done along with P4b gene sequences of other avipox viruses. Phylogenetic analysis showed that this avipox virus obtained from pigeon was grouped under sub-clade A2 along with other pigeonpox viruses. This confirmed that the causative agent of the avipox infection observed in pigeon was pigeonpox virus.